Probing Indonesian Teachers’ Learning Investment in Response to Educational Disruption: A Narrative Inquiry - Masayu Lely Mutmainnah; Sary Silvhiany; Eryansyah Eryansyah (VELES Voices of English Language Education Society, 2022)
Drawing upon the theoretical framework of investment and the methodological perspective of narrative inquiry, this article explores how English teachers from South Sumatra, Indonesia navigated the challenges of the sudden shift to online learning, how they positioned themselves in times of pandemic crisis professionally, and the perceived effects of their professional development participations. Data from the study include interviews, teachers’ digital artifacts, and teachers’ reflective writing. The critical incident analysis employed in this study sheds light on the challenges faced by English teachers in teaching online in the pandemic era including the unavailability of internet quota at home, teachers’ difficulties in teaching online, and the ability of teachers to adapt online teaching. Besides, the English teachers invested in continuing professional development by applying professional development activities such as; seminars, webinars, training, and workshop that were facilitated by the government and shared in the social group such as MGMP activities. Lastly, professional development was important for them since it affected their teaching online during a pandemic and their professional competency development and performance during online teaching activities. Implications are drawn out for school administration, governmental education departments, and teacher education institutions, as they need to coalesce to engage in more collaborative work to support teachers’ professional development.